Internalization Of Learning Concepts According To Imam Az Zarnuji In Determining The Influence Of Modernization On Elementary Students - Muhamad Khanif Alaudin; Rosichin Mansur (Abjadia : International Journal of Education, 2023)
This research study was conducted to identify the efforts made by educational institutions in fortifying students or their students in living an increasingly modern and advanced life in terms of economy, education, and industry. By instilling salafi learning values or concepts that become a reference for students' moral values. The form of business that is carried out clearly must be systematic and with many considerations. Because the next generation is an investment in the nation's future, which in the future they will lead the State of Indonesia. Thus, modern needs to be done without building a generation so as not to be contaminated with bad moral values, which is an obligation that falls under the responsibility of all elements of the school community and the family environment in particular. So that the noble goals of character education are encouraged to be successful so that later in welcoming the golden generation in 2045 they will be ready and strong in their moral values.